Metodologías educativas y su aporte en el proceso de enseñanza de herramientas tecnológicas en los estudiantes de la carrera de Pedagogía de la Actividad Física y Deporte de la Universidad Técnica de Babahoyo, diciembre 2022 - abril 2023 - Ramos Quezada, Merlyn Aracely (2023)
The integration of technologies in education is one of the main transformations that have been taking place in recent years; That is why the purpose of this research project is to determine the educational methodologies that affect the teaching process of technological tools in students of the Pedagogy of Physical Activity and Sport career; To achieve this objective, techniques such as: bibliographic research and survey were used, having a study sample of 12 Teachers belonging to the Pedagogy of Physical Activity and Sport career; As a conclusion, it was obtained that: the implementation of innovative educational methodologies and technologies in the teaching process of technological tools in the students of the Physics and Sports Pedagogy Career of the Technical University of Babahoyo can be an effective strategy to improve quality. Of learning and encourage students' independence and critical thinking. In addition, it is evident that the methodology based on Flipped Classroom and the use of online learning platforms and mobile applications are valuable tools for teaching and learning in this career.